IDENTIFICATION LOCATION FEASIBILITY AND SERVICE COVERAGE OF FSTP USING GEOGRAPHIC INFORMATION SISTEM (GIS) IN BANDUNG CITY - Tesyana Widodo, Happy
Bandung as one of the city in Indonesia which already has an urban sewerage sistem has not been able to meet the target of Sustainable Development Goals (SDGs) to provide adequate and equitable sanitation and hygiene for all and end open defecation (OD). This is proven by the number of OD practices in 2017 of 40.13%,. In order to support the strategy of Bandung City Sanitation Working Group that is improving and developing FSTP, the research to identify the location feasibility and FSTP scope of services using Geographic Information Sistem (GIS) in Bandung City is conducted. This research begins with identification of the criteria and their weight in determining the FSTP location using pairwise comparison analysis to 31 respondents from stakeholders in Jakarta, Bandung, Depok, Bekasi, and Yogyakarta on five criteria namely technical, institutional, regulatory and policy, financial, and community acceptance. The identified criteria were mapped and intersected using GIS. There are three plans of FSTP located in Gedebage, Cinambo, and Andir Districts with score of more than 341. Using these three plans of FSTP, three scenarios were formed with different number of FSTP in each scenario and each scenario exceeds the minimum requirement of FSTP area of Bandung City in 2041 which is 26,400 m 2 refers to the technology used in Gumuruh FSTP. The FSTP location in the 1st to 3rd scenario are in Gedebage District, Gedebage and Cinambo Districts, and Gedebage, Cinambo, and Andir Districts. Network analysis was performed to the 3 scenarios and the result showed that not all area in Bandung City that has not been served by urban sewerage sistem could be included in the FSTP scope of services because of the inadequate access. Then, the nearest distance and shortest travel time to the farthest service coverage occur in the 3rd scenario so the 3rd scenario get the highest final score of 437.